2019
DOI: 10.1088/1742-6596/1417/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Ancient China history-based task to support students’ geometrical reasoning and mathematical literacy in learning Pythagoras

Abstract: This study aims to identify the potential learning opportunities provided by ancient china’s geometric diagram introduced by Liu Hui into student task in learning Pythagorean theorem. We investigate the role of the history-based task, from Nine Chapter, in supporting students’ mathematics literacy and geometrical reasoning. Design research was chosen as a method to reach the purpose. Our discussion is limited only from a part of one phase, namely pilot experiment, from three main phases of design research. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Additionally, the learning design with contextual problem integrated has the potential to enhance students' fundamental mathematical capabilities, such as reasoning, argumentation, and mathematizing (Kusumawati et al, 2022). Numerous studies have demonstrated that contexts can improve students' mathematical comprehension, including historical ones, (Fachrudin et al, 2019;2020a;2020b), culture-based context (Samo, Darhim, & Kartasasmita, 2018), Indonesian traditional game (Jaelani et al, 2013) and even in a financial context (Sawatzki, 2017). The other study also confirmed that the use of context also increases students' confidence (Fauzan et al, 2018) and ability in reasoning in learning social arithmetic (Fauzan et al, 2018;Risdiyanti et al, 2019).…”
Section: Teachermentioning
confidence: 99%
“…Additionally, the learning design with contextual problem integrated has the potential to enhance students' fundamental mathematical capabilities, such as reasoning, argumentation, and mathematizing (Kusumawati et al, 2022). Numerous studies have demonstrated that contexts can improve students' mathematical comprehension, including historical ones, (Fachrudin et al, 2019;2020a;2020b), culture-based context (Samo, Darhim, & Kartasasmita, 2018), Indonesian traditional game (Jaelani et al, 2013) and even in a financial context (Sawatzki, 2017). The other study also confirmed that the use of context also increases students' confidence (Fauzan et al, 2018) and ability in reasoning in learning social arithmetic (Fauzan et al, 2018;Risdiyanti et al, 2019).…”
Section: Teachermentioning
confidence: 99%
“…It can be seen in Figure 3, the national exam questions in China contain questions with a reasoning ability above 30%. The test questions focus on creating problem situations to promote the improvement of students' mathematics literacy (Dinni, 2018;Fachrudin et al, 2019;Retnawati & Wulandari, 2019). Through…”
Section: Reasoning Abilitymentioning
confidence: 99%
“…HPM is the relationship between the history of exponential science and mathematics education (Fachrudin et al, 2019;Feigenberg, 2002). It appeared as an academic research field since 1972.…”
Section: Introductionmentioning
confidence: 99%